2022
DOI: 10.1093/sleep/zsac301
|View full text |Cite
|
Sign up to set email alerts
|

Atypical hypnotic compound ML297 restores sleep architecture immediately following emotionally valenced learning, to promote memory consolidation and hippocampal network activation during recall

Abstract: Sleep plays a critical role in consolidating many forms of hippocampus-dependent memory. While various classes of hypnotic drugs have been developed in recent years, it remains unknown whether, or how, some of them affect sleep-dependent memory consolidation mechanisms. We find that ML297, a recently-developed candidate hypnotic agent targeting a new mechanism (activating GIRK1/2-subunit containing G-protein coupled inwardly rectifying potassium [GIRK] channels), alters sleep architecture in mice over the firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…We (1113) and others (9, 10) have previously shown that sleep deprivation (SD) over the hours immediately following CFC results in disrupted CFM consolidation. We confirmed these disruptive effects in the cfos::tdTomato mouse line.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…We (1113) and others (9, 10) have previously shown that sleep deprivation (SD) over the hours immediately following CFC results in disrupted CFM consolidation. We confirmed these disruptive effects in the cfos::tdTomato mouse line.…”
Section: Resultsmentioning
confidence: 94%
“…In both animal models and human subjects, sleep deprivation (SD) negatively impacts consolidation of hippocampus-dependent memories (5)(6)(7). For example, in mice, consolidation of contextual fear memory (CFM), a canonical form of Pavlovian conditioning (8) is disrupted by SD in the first 5-6 h following single-trial contextual fear conditioning (CFC; pairing exploration of a novel context with a foot shock) (9)(10)(11)(12)(13). Recent studies have shown that SD can alter basic features of hippocampal network function, including oscillatory patterning of network activity (11), intracellular signaling (10,14,15), transcription and translation (12,(16)(17)(18)(19), and excitatoryinhibitory balance (20,21).…”
Section: Introductionmentioning
confidence: 99%
“…No novel objects or additional sensory stimuli were provided, to limit sensory-based neocortical plasticity during sleep deprivation procedures 101 . To estimate the amount of sleep lost in BR + SD mice, BR + Sleep mice were visually monitored every 5 min over the first 4 h following visual enrichment for assumption of sleep postures, similar to previous studies 83,[102][103][104] . As previously described, similar procedures used for sleep deprivation in adult mice 105 and critical period cats 8 either have no significant effect on serum cortisol, or increases it to a degree that is orders of magnitude lower than that capable of disrupting ODP 106 .…”
Section: Methodsmentioning
confidence: 99%
“…Together, these findings suggest that NREM-associated suppression of ACh input to hippocampus is an essential feature for sleep-dependent memory consolidation. However, there are accumulating data suggesting that REM -a high-ACh brain state -also plays an important role in consolidation of hippocampus-dependent memories (59)(60)(61)(62). Yet it remains unclear whether NREM and REM play overlapping, distinct, or complementary roles in the storage of information in neural networks.…”
Section: Introductionmentioning
confidence: 99%